A enfermagem frente a acidentes de trabalho com material potencialmente contaminado na era do HIV The nursing team and occupational accidents with potentially contaminated material in the era of HIV - Elucir Gir; Fabiana Prado Potiens Costa; Adriana Maria da Silva (SciELO, 1998)
Realizou-se esta investigação, com os objetivos de identificar a ocorrência de acidentes de trabalho com material pérfuro-cortante potencialmente contaminado, entre enfermeiros e auxiliares de enfermagem de um Hospital de ensino geral do interior do Estado de São Paulo; relacionar a ocorrência destes acidentes com a categoria profissional e anos de trabalho na instituição; identificar o tipo de material pérfuro-cortante causador do acidente e identificar as condutas tomadas após o acidente, pelo acidentado. Para a coleta de dados, através de entrevista individual, utilizou-se um formulário estruturado onde registrava-se, a causa atribuída ao acidente, o período de atuação do profissional acidentado, o objeto causador, a conduta tomada após o acidente. Evidenciou-se que as Precauções Padrão ou as antigas Precauções Universais não são utilizadas como deveriam, conferindo portanto, risco à equipe de enfermagem. Considera-se que esta equipe necessita de orientações específicas através de educação continuada sobre o assunto. This investigation was carried out in order to: identify the occurrence of professional accidents with perforate cutting potentially contaminated material among nurses and nursing auxiliaries that work in a general teaching hospital in the interior of the state of São Paulo. The other objectives were: to associate the occurrence of accident with the professional category and period of work; to identify the type of perforate cutting material most involved in accidents, to identily the attitudes taken by the person accidented. The data were collected on individual interview based on a structured formulary in which the following information was registered: the probable reason of accident, how long the professional has been working on such function, the material involved in the accident, the actions taken after the accident. It was evidenced that the Standard Precautions or the Universal Precautions as they used used to be nominated are not being used as they should be. Such attitude brings risks to the nursing team. We think that this team needs specific orientations through continuing education concerning the theme.